Unraveling regulatory divergence, heterotic malleability, and allelic imbalance switching in rice due to drought stress - Ereful, Nelzo C.; Laurena, Antonio; Liu, Li-Yu; Kao, Shu-Min; Tsai, Eric; Greenland, Andy; Powell, Wayne; Mackay, Ian; Leung, Hei (Springer, 2021)
The indica ecotypes, IR64, an elite drought-susceptible variety adapted to irrigated ecosystem, and Apo (IR55423-01 or NSIC RC9), a moderate drought-tolerant upland genotype together with their hybrid (IR64 × Apo) were exposed to non- and water-stress conditions. By sequencing (RNA-seq) these genotypes, we were able to map genes diverging in cis and/or trans factors. Under non-stress condition, cis dominantly explains (11.2%) regulatory differences, followed by trans (8.9%). Further analysis showed that water-limiting condition largely affects trans and cis + trans factors. On the molecular level, cis and/or trans regulatory divergence explains their genotypic differences and differential drought response. Between the two parental genotypes, Apo appears to exhibit more photosynthetic efficiency even under water-limiting condition and is ascribed to trans. Statistical analyses showed that regulatory divergence is significantly influenced by environmental conditions. Likewise, the mode of parental expression inheritance which drives heterosis (HET) is significantly affected by environmental conditions indicating the malleability of heterosis to external factors. Further analysis revealed that the HET class, dominance, was significantly enriched under water-stress condition. We also identified allelic imbalance switching in which several genes prefer IR64- (or Apo-) specific allele under non-stress condition but switched to Apo- (or IR64-) specific allele when exposed to water-stress condition.